PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN MENULIS PUISI SISWA SEKOLAH DASAR - Jainatun Naimah, Hidayatul Munawwarah S, Barita Esman Dabukke (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study was motivated by the low poetry writing skills of students in Indonesian language learning. The objective of the study is to determine the ef ect of contextual teaching model on the poetry writing skills of fourth-grade students at SDN 066652 Medan Helvetia. This research employs a quantitative method using a pre-experimental design with a one-group pretest-posttest approach. The population consisted of all 26 fourth-grade students at SDN 066652 Medan Helvetia, and the sample was selected using a total sampling technique. The instrument used was a poetry writing test based on specific assessment indicators. Data analysis results showed that the average pretest score was 46.31, while the average posttest score increased to 88.94. The t-test results revealed a significance value (2-tailed) of 0.000 < 0.05, with a t-value of 11.473 and a t-table value of 1.708 (t-value > t-table), indicating that the null hypothesis is rejected and the alternative hypothesis is accepted. Therefore, it can be concluded that the application of the contextual teaching model has a significant ef ect on the poetry writing skills of fourth-grade students at SDN 066652 Medan Helvetia.